Preventive treatment with guarana powder (Paullinia cupana) mitigates acute paracetamol-induced hepatotoxicity by modulating oxidative stress - Clécia Dias Teixeira; Priscila Oliveira Barbosa; Wanderson Geraldo Lima; Gustavo Silveira Breguez; Miliane Martins de Andrade Fagundes; Daniela Caldeira Costa; Cintia Lopes de Brito Magalhães; Joana Ferreira Amaral; Melina Oliveira de Souza (Toxicology Reports)
Liver damage caused by high doses of paracetamol is a global public health concern. Consequently, therapeutic strategies are being explored to prevent this damage. The bioactive compounds present in fruits have shown promise in protecting against disorders associated with paracetamol-induced liver damage. This study assessed the preventive effects of guarana powder on redox status in a rat model of acute hepatotoxicity induced by a toxic dose of paracetamol. Male Wistar rats were divided into four groups: control (C), guarana (G), paracetamol (P), and guarana + paracetamol (GP). Animals in groups G and GP received 300 mg/kg guarana powder daily for seven days. Hepatotoxicity was induced in the P and GP groups by a single dose of 3 g/kg paracetamol on the last day. Paracetamol effectively induced liver damage and oxidative stress in group P animals. Preventive treatment with guarana significantly mitigated this damage and prevented the serum elevation of ALT, AST, and ALP by 44 %, 29 %, and 24 %, respectively. It also prevented a 133 % increase in the necrotic liver area in GP animals compared to the P. Guarana treatment, which prevented reductions in glutathione levels, modulated antioxidant enzyme (SOD and CAT) expression and activity, and protein carbonylation, while enhancing the total antioxidant capacity. Our results suggest that preventive treatment with guarana can attenuate oxidative damage, modulate antioxidant defense gene expression, and protect against paracetamol-induced hepatotoxicity in rats, highlighting guarana powder as a potential therapeutic agent to prevent liver damage induced by high doses of paracetamol.